Metastatic Merkel cell carcinoma response to nivolumab. Issue 1 (December 2016) - Walocko, Frances; Scheier, Benjamin; Harms, Paul; Fecher, Leslie; Lao, Christopher
Abstract Background Merkel cell carcinoma (MCC) is an aggressive cutaneous neuroendocrine malignancy with limited treatment options. Several lines of evidence support the programmed death-1/programmed death-ligand 1 (PD-1/PD-L1) axis as a likely contributor to immune evasion in MCC. Case presentation We report a case of a patient with metastatic MCC with a significant and durable response to nivolumab, a humanized IgG4 monoclonal anti-PD-1 antibody. Conclusion Immunotherapy with PD-1/PD-L1 inhibitors has become a rational and promising treatment option for MCC in the advanced or metastatic disease. Clinical trials are currently in progress to further evaluate these novel therapeutic agents.